Association of serum mimecan with angiographic coronary collateralization in patients with stable coronary artery disease and chronic total occlusion. (September 2016) - Shen, Ying; Ding, Feng Hua; Zhang, Rui Yan; Zhang, Qi; Lu, Lin; Shen, Wei Feng
Abstract: Background and aims: Mimecan/osteoglycin is identified as an emerging biomarker of coronary atherosclerosis. We investigated whether and to what extent serum mimecan reflects angiographic coronary collateralization in patients with stable coronary artery disease and chronic total occlusion. Methods: Serum levels of mimecan were determined in 559 consecutive patients with stable angina and angiographic total occlusion of at least one major coronary artery. The degree of collaterals supplying the distal aspect of a total occlusion from the contra-lateral vessel was graded as poor (Rentrop score of 0 or 1) or good coronary collateralization (Rentrop score of 2 or 3). Results: Serum mimecan was significantly higher in patients with poor collateralization than in those with good collateralization, and correlated inversely with Rentrop score (adjusted Spearmen's r = −0.443, p  < 0.001). The prevalence of poor coronary collaterals increased stepwise from the lowest to the highest quartile of serum mimecan (OR 2.140, 95% CI 1.793–2.555; p for trend < 0.001). After adjusting for age, gender, traditional risk factors for coronary artery disease, history of myocardial infarction, severity of coronary artery disease, renal function and C-reactive protein, serum mimecan (per SD) remained an independent determinant for poor collateralization (OR 2.674, 95% CI 2.057–3.475, p  < 0.001). The diagnostic value of mimecan (per SD) for detecting poor collateralization was consistent when the patients were specified by gender, age, body mass index, presence or absence of hypertension and diabetes, and status of renal function (OR 2.075–6.932, p interaction ≥ 0.059). Conclusion: Increaseds erum mimecan is associated with poor angiographic coronary collateralization in patients with chronic total occlusion. Highlights: The relation between serum mimecan level and coronary collateralization is evaluated. Mimecan level correlates inversely with Rentrop score of collateralization. Serum mimecan level is an independent determinant for poor collateralization. Mimecan could be a biomarker of coronary collateral in CAD patients.